BloombergQuint : growing users with WhatsApp - Abhishek, (SAGE Business. Cases., 2019)
BloombergQuint (BQ), a financial and business news provider, was launched as a joint venture between Quintillion Media (QM) and Bloomberg in April 2016. In the competitive landscape of business news broadcasting in India, BQ started out by providing stock updates, financial sector news and opinion articles on financial issues on its website. It began delivering video content in September 2017. It had applied for a television broadcasting licence and awaited approval from the Indian Ministry of Information and Broadcasting. Lacking a television presence, BQ found it necessary to use alternate distribution channels to ensure that its content reached a wider audience.